INTERPOLATION BY TRANSLATES OF A 1/x FUNCTION WITH ENERGY CONSTRAINT - Pramesti, Dita
This thesis discusses a new interpolation method that uses translates of o(x) = 1=x as interpolants. The proof of f1=(x - vj) nj=1 as interpolants is shown using the fact that the Cauchy matrix is nonsingular. The function that is obtained as an interpolation result is a linear combination of n-translates of o(x). To choose translation factors, minimum energy principle is used to obtain the best curve as an interpolation result. The results show that the energy decreases when the distance and spread of translation factors increase. A procedure to find translation factors that optimize the energy of the curve is presented in this thesis.